Respuestas fisiológicas sobre el aprendizaje de habilidades de Krabi-Krabong en estudiantes de la provincia de Buriram - Wandee, Amorntheap; Chabairam, Ban; Homjan, Suchart (Retos, 2025)
Objective: This research aimed to analyze the electromyographic (EMG) responses during Mai Ram Krabi-Krabong and striking techniques from an exercise physiology perspective, and to compare physiological responses in students of Buriram province who received Krabi-Krabong training and those who did not.Method: The study was conducted in two phases: the first examined EMG responses during Krabi-Krabong techniques, while the second developed and studied the effects of Krabi-Krabong instruction in physical education classes. The study involved two groups of participants. The first group in study 1 consisted of 16 university students skilled in Krabi-Krabong techniques, who participated in the EMG analysis. The second group in study 2 comprised 50 high school students, divided equally into a control group receiving standard physical education instruction and an experimental group receiving Krabi-Krabong training. Both groups participated in weekly 50-minute sessions for 12 weeks. Assessments included computerized cognitive tests, and physical fitness tests.Results: Results from the first study revealed the activation of specific muscle groups during 12 Mai Ram (16 sequences) and 5 striking techniques, emphasizing the full-body engagement of Krabi-Krabong. The second study found significant improvements in physical fitness, including upper body strength, cardiovascular endurance, leg muscle endurance, hand-forearm strength, static balance, and Krabi-Krabong skills in the experimental group. Additionally, Krabi-Krabong training enhanced executive functions in cognitive flexibility, inhibitory control, attention, and creativity, with all improvements being statistically significant at the .05 level.Conclusions: Krabi-Krabong training significantly improves physical fitness and cognitive function in students.